La simbiótica relación de dos arqueólogos con trayectorias divergentes y objetivos comunes en el último tercio del siglo XIX. José Ramón Mélida y Emil Hübner - Casado Rigalt, Daniel (Madrider Mitteilungen, 2020)
Between the German and Spanish Archaeology of the second half of the 19th century, there is a considerable distance on both academic and scientific levels. Nevertheless, the contact between archeologists of both countries helped to shorten this distance. One good example is the professional relationship between Emil Hübner and José Ramón Mélida, two of the most representative archeologists of the last third of the 19th century, and whose paths, in spite of the generational gap, contain the necessary keys to assess the Spanish Archaeology of the moment. Spain imported the German scientific and technical talent due to the fact that investigators of Hübner’s stature joined the Spanish academic and museological structures, therefore gaining access to collections and archaeological sites.